2019
DOI: 10.1093/mnras/stz3629
|View full text |Cite
|
Sign up to set email alerts
|

The Hubble Space Telescope UV Legacy Survey of Galactic globular clusters – XXI. Binaries among multiple stellar populations

Abstract: A number of scenarios for the formation of multiple populations in globular clusters (GCs) predict that second generation (2G) stars form in a compact and dense subsystem embedded in a more extended first-generation (1G) system. If these scenarios are accurate, a consequence of the denser 2G formation environment is that 2G binaries should be more significantly affected by stellar interactions and disrupted at a larger rate than 1G binaries. The fractions and properties of binary stars can thus provide a dynam… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…Additional support for the hot-hydrogen burning hypothesis comes from the fact that some GCs display broadened or split main sequences in the colour magnitude diagram (Anderson 2002;Bedin et al 2004;Piotto et al 2007Piotto et al , 2012Han et al 2009), which has been attributed to He spreads (Norris 2004;D'Antona et al 2005;Charbonnel 2016; Lagioia et al 2019). More recently, the so-called chromosome map was introduced, which is based on specific combinations of HST filters that are sensitive to He and N ; it turns out to be a very powerful photometric tool to detect the presence of multiple stellar populations in Galactic and extra-galactic GCs (Milone et al 2017;Zennaro et al 2019;Saracino et al 2019). In the last few years, evidence for N enhancement has been found in younger clusters ( 2 Gyr) in the Magellanic Clouds (e.g., Hollyhead et al 2017;Martocchia et al 2018a,b).…”
Section: The Rich Chemical Footprints Of Gcs and Viable Channels To Their Originmentioning
confidence: 99%
See 2 more Smart Citations
“…Additional support for the hot-hydrogen burning hypothesis comes from the fact that some GCs display broadened or split main sequences in the colour magnitude diagram (Anderson 2002;Bedin et al 2004;Piotto et al 2007Piotto et al , 2012Han et al 2009), which has been attributed to He spreads (Norris 2004;D'Antona et al 2005;Charbonnel 2016; Lagioia et al 2019). More recently, the so-called chromosome map was introduced, which is based on specific combinations of HST filters that are sensitive to He and N ; it turns out to be a very powerful photometric tool to detect the presence of multiple stellar populations in Galactic and extra-galactic GCs (Milone et al 2017;Zennaro et al 2019;Saracino et al 2019). In the last few years, evidence for N enhancement has been found in younger clusters ( 2 Gyr) in the Magellanic Clouds (e.g., Hollyhead et al 2017;Martocchia et al 2018a,b).…”
Section: The Rich Chemical Footprints Of Gcs and Viable Channels To Their Originmentioning
confidence: 99%
“…As mentioned earlier, the O-Na anti-correlation is so ubiquitous that it has been suggested to be the unique identifying property of a genuine GC (Carretta et al 2010). The ubiquity does not mean that all GCs are similar; quite the contrary, the details of the multiple populations are different in every GC (Milone et al 2017). Some note-worthy trends with GC properties have been identified, that might provide clues to the origin of these multiple populations.…”
Section: The Rich Chemical Footprints Of Gcs and Viable Channels To Their Originmentioning
confidence: 99%
See 1 more Smart Citation
“…In Milone et al (2017), the fraction of first generation stars was shown to anti-correlate with cluster mass and Lucatello et al (2015) showed that the more Helium poor first generation stars have a higher binary fraction compared to second generation stars. However, the results of the recent study by Milone et al (2020) suggest equal binary fractions for the majority of clusters. Also, the internal Helium abundance varies significantly between first and second generation stars for some clusters (Milone et al 2018).…”
Section: The Relation Of Helium To Further Cluster Parametersmentioning
confidence: 86%
“…Extending our analysis to other detection techniques for binaries will provide a better link between the estimated binary fraction and kinematics effects of binaries. To do so, we first need to consider multiple populations in the simulations (Hong et al 2015) as they play a relevant role in the photometric binary detection (Milone et al 2020). At the same time, it is necessary to check the different biases in the detection methods: radial velocity methods mainly detect binaries with short periods, whereas photometric methods depend on the mass ratio of binaries (Milone et al 2012).…”
Section: Discussionmentioning
confidence: 99%